Composite Hemangioendothelioma With Neuroendocrine Marker Expression: Report of a "Paraganglioma-Like" Paravertebral Case. (October 2020) - Cheuk, W.; Shum, K. S.; Ng, W. K.; Chan, John K. C.
Composite hemangioendothelioma is a rare vascular tumor morphologically comprising several distinct vascular components and exhibits a borderline malignant potential. We described the case of a 53-year-old female who presented with an infiltrative mass in the paravertebral soft tissue. The tumor showed discrete nests of synaptophysin-expressing epithelioid cells accompanied by rich vasculature, features highly reminiscent of sympathetic paraganglioma. Further analysis revealed areas resembling spindle cell hemangioma, retiform hemangioendothelioma, cavernous hemangioma/lymphangioma, and epithelioid hemangioendothelioma without the myxohyaline matrix in the tumor, and a final diagnosis of composite hemangioendothelioma with synaptophysin expression was made. Critical appraisal of this recently described entity and its possible pathogenic relationship with retiform hemangioendothelioma were discussed.